The intention to start a business among UiTM, Segamat students: a case study in Suruhanjaya Syarikat Malaysia (SSM) / Muhammad Fauzan Arief Abd Razak - Abd Razak, Muhammad Fauzan Arief (2017)
The purpose of this study is done is to determine what are the intention to start a business among UiTM Segamat students. Researcher has collected both primary and secondary which conducted a quantitative method that used 100 respondents through google doc. The researcher then analyzed the data using Statistical Package for Social Science (SPSS) software. The results showed that after conducting using SPSS the most significant factors which related to the intention of starting a business are the Subjective Norms, and the rest of the factor that is Sources of Financial, Job Opportunity, Attitude and Perceived Behavior Control which the researcher found out that it is not significant.